Investigating differences in project activities and student digital literacy between learning through electronic workbench and PhET Simulation - Susilawati, Susilawati; Azizah, Nisa Awaliyah Nur; Kusuma, Hamdan Hadi (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2021)
Students' digital literacy is very urgent for online learning and requires learning activities for habituation. The purpose of this study was to investigate the comparison of project activity processes and digital literacy, between learning using electronic workbench and PhET simulation. This research method uses a quasi-experimental design, the sample consists of two groups, namely 29 students in the experimental group and 31 students in the control groupselected through purposive sampling techniqueThe data collection technique used a concept understanding test part of digital literacy, observation of the results of project activities and questionnaires about digital literacy. The data analysis technique used inferential analysis and quantitative descriptive analysis. This study uses two applications, namely electronic workbench in the experimental group and PhET simulation in the control group. The differences identified from the aspect of understanding concepts part of digital literacy and practical procedures. This research shows that the practicum process in a virtual laboratory using an electronic workbench N-gain a better conceptual understanding of literacy and laboratory skills related to practical procedures. In the process of implementing the practicum using an electronic workbench, experience is obtained in carrying out more thorough and accurate practicum procedures. In addition, this virtual practicum requires an adequate understanding of the concept of electronic components and the relationship between the measured electrical quantities.